Screening for malnutrition in nursing home residents: comparison of different risk markers and their association to functional impairment - Stange, Inken; Pöschl, Karin; Stehle, Peter; Sieber, Cornel; Volkert, Dorothee (Journal of Nutrition, Health & Aging, 2013)
OBJECTIVES To identify nursing home residents with malnutrition or at risk of malnutrition by using different markers, determine if the Mini Nutritional Assessment (MNA®) is able to identify all residents at risk according to single risk markers and explore the relation between risk markers and functional impairment. DESIGN Cross-sectional study. SETTING Six German nursing homes. PARTICIPANTS 286 residents (86±7y, 89% female). MEASUREMENTS Screening for malnutrition or its risk included low BMI (≤22 kg/m²), recent weight loss (WL), low food intake (LI) as single risk markers and MNA (<24 points, p.) as composite marker. Prevalence of single nutritional risk markers in different MNA categories was compared by cross-tables. Mental (cognition, mood) and physical function (mobility) were assessed by interviewing nursing staff and association of impaired status to nutritional risk markers determined by Chi² test. RESULTS 32.9% of residents had a low BMI, 11.9% WL and 21.3% LI. 60.2% were categorized malnourished (18.2%) or at risk of malnutrition (42.0%) by MNA. 64% presented at least one of these nutritional risk markers. Of those classified malnourished by MNA, 96.2% also showed low BMI, WL or LI. In contrast, eleven residents (9.6%) considered well-nourished by MNA presented single risk markers (9 low BMI, 2 WL). Cognitive impairment, depressive symptoms and immobility was present in 59.0%, 20.8% and 25.5%, respectively. Functional impairment, and in particular severe impairment, was to a higher proportion present in residents at nutritional risk independent of the chosen marker (MNA<24 p., low BMI, WL, LI). CONCLUSION The high prevalence of nutritional risk highlights the importance of regular screening of nursing home residents. The MNA identified nearly all residents with low BMI, WL and LI. The close association between nutritional risk and functional impairment requires increased awareness for nutritional problems especially in functionally impaired residents, to early initiate nutritional measures and thus, prevent further nutritional and functional deterioration.